2022
DOI: 10.3389/fnagi.2022.875261
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome in Parkinson’s Disease: A Longitudinal Study of the Impacts on Disease Progression and the Use of Device-Assisted Therapies

Abstract: BackgroundAltered gut microbiome (GM) composition has been established in Parkinson’s disease (PD). However, few studies have longitudinally investigated the GM in PD, or the impact of device-assisted therapies.ObjectivesTo investigate the temporal stability of GM profiles from PD patients on standard therapies and those initiating device-assisted therapies (DAT) and define multivariate models of disease and progression.MethodsWe evaluated validated clinical questionnaires and stool samples from 74 PD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 78 publications
2
35
0
Order By: Relevance
“…In 2021, Cilia et al showed that a shortage of Roseburia in de novo PD patients was predictive of a faster deterioration in motor, non-motor, and intellectual ability within 3 years [ 160 ]. Similar results were then obtained by Lubomski et al who reported that low levels of Barnesiella at the baseline and at 1-year follow-up were associated with a worse clinical evolution of PD [ 51 ]. Furthermore, a machine learning approach accounting for the abundance of various gut microbial species revealed that a reduction in Fusicatenibacter , Blautia and Faecalibacterium , together with an increased presence of Akkermansia , correlates with a faster progression of the disease [ 166 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Biomarkers And Drug ...supporting
confidence: 84%
See 1 more Smart Citation
“…In 2021, Cilia et al showed that a shortage of Roseburia in de novo PD patients was predictive of a faster deterioration in motor, non-motor, and intellectual ability within 3 years [ 160 ]. Similar results were then obtained by Lubomski et al who reported that low levels of Barnesiella at the baseline and at 1-year follow-up were associated with a worse clinical evolution of PD [ 51 ]. Furthermore, a machine learning approach accounting for the abundance of various gut microbial species revealed that a reduction in Fusicatenibacter , Blautia and Faecalibacterium , together with an increased presence of Akkermansia , correlates with a faster progression of the disease [ 166 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Biomarkers And Drug ...supporting
confidence: 84%
“…Concerning PD, dysbiosis followed by GI symptoms and gut discomfort far precedes the onset of motor dysfunctions and it is linked to neuroinflammation, as well as to alterations in dopamine, serotonin, and kynurenine metabolism through the gut-brain axis [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ] ( Figure 1 ). Similar to what has been reported in Alzheimer’s disease (AD) and aging [ 30 ], feces from PD patients are enriched in opportunistic pathogens and pro-inflammatory taxa at the expense of anti-inflammatory microbes and SCFAs-producing bacteria, especially butyrate [ 47 , 48 , 49 , 50 , 51 ]. Accordingly, meta-analysis and systematic reviews report that PD patients are characterized by an overgrowth of the genera Bifidobacterium , Lactobacillus , Akkermansia and of the opportunistic pathogens Porphyromonas and Corynebacterium , together with a decreased abundance of the SCFAs producers Prevotellaceae , Lachnospiraceae and Faecalibacterium [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Links And Mechanismsmentioning
confidence: 80%
“…Evidence from a number of research groups ( Hasegawa et al, 2015 ; Keshavarzian et al, 2015 ; Sampson et al, 2016 ; Bedarf et al, 2017 ; Hill-Burns et al, 2017 ; Aho et al, 2019 ; Romano et al, 2021 ; Lubomski et al, 2022 ; Zhu et al, 2022 ) has emerged proposing a relationship between the gut microbiota and PD. The study by Killinger et al (2018) proposed that the normal human vermiform appendix harbors pathogenic forms of α-synuclein that affect the risk of developing PD and that an appendectomy could be a potential prophylactic for initiation of PD.…”
Section: Neurodegenerative Diseases and The Microbiota-gut-brain Axismentioning
confidence: 99%
“…Four longitudinal studies investigated the gut microbiome of already treated PD subjects at baseline and after one to two years. [27][28][29][30] Gut microbiome composition apparently remained stable in studies using 16S rRNA gene sequencing, whereas total fecal bacterial counts were decreased after two years in one study using quantitative reverse-transciption polymerase chain reaction (qRT-PCR) of selected taxa. Therefore, an exposure period of more than 90 days, but less than two years, seems appropriate to investigate the effect of PD medication on gut microbiome composition.…”
Section: Introductionmentioning
confidence: 99%